H1 Hemagglutinin Priming Provides Long-Lasting Heterosubtypic Immunity against H5N1 Challenge in the Mouse Model - Juan Manuel Carreño (American Society for Microbiology, 2020)
ABSTRACT Influenza virus infections leave a signature of immune memory that influences future responses to infections with antigenically related strains. It has been hypothesized that the first exposure in life to H1N1 influenza virus imprints the host immune system, potentially resulting in protection from severe infection with H5N1 later in life through hemagglutinin (HA) stalk-specific antibodies. To study the specific role of the HA on protection against infection without interference of cellular immunity or humoral antineuraminidase immunity, we primed mice with influenza B viruses that express an H1 HA (group 1; B-H1), H3 HA (group 2; B-H3), or wild-type influenza B virus and subsequently challenged them at different time points with an H5N1 virus. Weight loss and survival monitoring showed that the B-H1-primed mice exhibited better protection against H5N1 compared to the control mice. Analysis of H5-specific serum IgG, before and 21 days after H5N1 challenge, evidenced the presence of anti-stalk H5 cross-reactive antibodies in the BH-1 group that were boosted by H5N1 infection. The increased immune responses and protection induced by priming with the B-H1 viruses lasted at least up to 1 year. Hence, a single HA priming based on natural infection induces long-lasting protective immunity against heterosubtypic strains from the same phylogenetic HA group in mice. This study gives mechanistic support to the earlier finding in humans that imprinting by H1 HA protects against H5N1 infections and that highly conserved regions on the HA, like the stalk, are involved in this phenomenon. IMPORTANCE Current studies point out that an HA-mediated immunological imprint is established early in life during the first exposure to influenza viruses, which critically shapes and biases future immune responses. However, studies in animal models are limited and the precise mechanisms of this phenomenon are under investigation. Studies that explore the effect of HA-specific immunity induced during natural infection on future exposures to heterosubtypic influenza strains are needed.